(untitled) (Research, Society and Development, 2022)
Objective: To know the understanding of academics entering health courses in relation to spirituality and religiosity in health care. Methodology: descriptive study of qualitative approach, with intentional convenience sampling. For the conception of the research, data related to the profile of the interviewees were collected, with application of the FICA instrument containing 04 evaluation domains: faith/belief, importance/influence, community and action in the treatment. Then, the data were analyzed by the content analysis technique. Results: The analysis of the results showed four categories: "Conception about faith/belief in the personal experience of the individual"; "The importance of religiosity and spirituality and the influence it plays on the daily lives of people and health professionals"; "How can the religious community contribute and assist in the life of society?" "How care provided in treatment should be seen by health professionals and how it may affect and/or contribute to therapy." Conclusion: It was found that most participants understand religiosity and spirituality as effective psychological resources for coping with unfavorable health situations.